2022
DOI: 10.1007/s00345-022-04124-x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of genitourinary complications following radiation therapy for localised prostate cancer

Abstract: Purpose Studies of genitourinary toxicity following radiotherapy for prostate cancer are mainly from high volume single institutions and the incidence and burden of treatment remain uncertain. Hence we determine the cumulative incidence of treatment-related genitourinary toxicity in patients with localised prostate cancer treated with primary external beam radiotherapy (EBRT) at a state population level. Methods We analysed data from a prospective populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
0
5
0
1
Order By: Relevance
“…However, the majority of included patients were treated with EBRT ≥ 2009 (62%), indicating mostly contemporary treatment techniques. Furthermore, the included clinical predictive factors remained significant in multivariable analysis adjusted for year of treatment, as demonstrated in our recently published article [29]. In addition, we do not have information regarding baseline IPSS, prostate volume or 5-ARI or alpha-blocker medication use before EBRT.…”
Section: Discussionmentioning
confidence: 86%
“…However, the majority of included patients were treated with EBRT ≥ 2009 (62%), indicating mostly contemporary treatment techniques. Furthermore, the included clinical predictive factors remained significant in multivariable analysis adjusted for year of treatment, as demonstrated in our recently published article [29]. In addition, we do not have information regarding baseline IPSS, prostate volume or 5-ARI or alpha-blocker medication use before EBRT.…”
Section: Discussionmentioning
confidence: 86%
“…Radiation-induced cystitis (RC) is a late-onset and under-reported condition after pelvic radiotherapy with an incidence rate of 5%–10%, even higher ( David et al . 2022 ).…”
Section: Radiation Toxicity and The Role Of Microbiotamentioning
confidence: 99%
“…Studies that tracked urinary AE revealed that about 4% of patients experienced severe AE [ 7 ]. When examining patients diagnosed with prostate cancer who solely received EBRT, a study performed by David et al revealed a 28.4% 10-year cumulative incidence rate of hospital admissions due to urinary AE [ 8 ]. The absence of studies presents a potential future area of exploration and collaboration among diverse disciplines and specialties.…”
Section: Prevalencementioning
confidence: 99%